2020
DOI: 10.1093/jncics/pkaa097
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping Cutaneous Melanoma Matters

Abstract: Background Our aim was to investigate the role of melanoma subtype on survival and focus on the effects stratified by Breslow thickness and ulceration status. Methods Patients with cutaneous melanoma stage I/II/III, diagnosed between 2000 and 2014 were derived from the Dutch Nationwide Pathology Registry and overall survival data from the Netherlands Cancer Registry. Patients were followed until 2018. Using multivariable Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 26 publications
6
33
0
Order By: Relevance
“…In an international investigation published by Dessinioti et al, 7 20.132 NM and SSM patients with thin tumors (≤ 1 mm) were analyzed. In line with the data of El Sharouni et al, 15 they found that thin NM, particularly between 0.8 mm and 1 mm tumor thickness, were associated with worse prognosis when compared to thin SSM tumors. 15,16 By contrast, Robsahm et al 17 did not observe that NM subtype is a signi cant independent predictor for melanoma-speci c survival (n = 5010, 2008 to 2012).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In an international investigation published by Dessinioti et al, 7 20.132 NM and SSM patients with thin tumors (≤ 1 mm) were analyzed. In line with the data of El Sharouni et al, 15 they found that thin NM, particularly between 0.8 mm and 1 mm tumor thickness, were associated with worse prognosis when compared to thin SSM tumors. 15,16 By contrast, Robsahm et al 17 did not observe that NM subtype is a signi cant independent predictor for melanoma-speci c survival (n = 5010, 2008 to 2012).…”
Section: Discussionsupporting
confidence: 86%
“…In line with the data of El Sharouni et al, 15 they found that thin NM, particularly between 0.8 mm and 1 mm tumor thickness, were associated with worse prognosis when compared to thin SSM tumors. 15,16 By contrast, Robsahm et al 17 did not observe that NM subtype is a signi cant independent predictor for melanoma-speci c survival (n = 5010, 2008 to 2012). They found an insigni cant hazard ratio of 1.01 (95% CI = 0.79 to 1.29) for NM.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In line with the data of El Sharouni et al (Sharouni et al 2020), they found that thin NM, particularly between 0.8 and 1 mm tumor thickness, were associated with worse prognosis when compared to thin SSM tumors (Sharouni et al 2020;Green et al 2012). In contrast, Robsahm et al (Robsahm et al 2018) did not observe that NM subtype is a significant independent predictor for melanoma-specific survival (n = 5010, 2008-2012).…”
Section: Discussionsupporting
confidence: 70%
“…They observed a hazard ratio for melanoma-specific death of 1.35 (95% CI = 1.08–1.70) for NM compared to SSM. In contrast, El Sharouni et al (EL Sharouni et al 2020 ) studied almost 50.000 MM patients, including approximately 80% primary SSM and about 15% primary NM. They observed that NM patients with tumors greater than 1 mm tumor thickness did not show worse survival than SSM patients with tumors greater than 1 mm.…”
Section: Discussionmentioning
confidence: 99%